Fiscal stimulus with learning-by-doing - Antonello D'Alessandro; Giulio Fella; Leonardo Melosi (Federal Reserve Bank of Chicago, 2018)
Using a Bayesian SVAR analysis, we document that an increase in government purchases raises private consumption, the real wage and total factor productivity (TFP) while reducing inflation. Each of these facts is hard to reconcile with both neoclassical and New-Keynesian models. We extend a standard New-Keynesian model to allow for skill accumulation through past work experience, following Chang, Gomes and Schorfheide (2002). An increase in government spending in- creases hours and induces skill accumulation and higher measured TFP and real wages in subsequent periods. Future marginal costs fall lowering future expected inflation and, through the monetary policy rule, the real interest rate. Consumption increases as a result.
Keywords: E62; E63; 330; Fiscal policy transmission; consumption; real wage